Malaria epidemiology and interventions in Ethiopia from 2001 to 2016 - Hiwot S Taffese; Elizabeth Hemming-Schroeder; Cristian Koepfli; Gezahegn Tesfaye; Ming-chieh Lee; James Kazura; Gui-Yun Yan; Guo-Fa Zhou (BMC, 2018)
Abstract Background Ethiopia is one of the African countries where Plasmodium falciparum and P. vivax co-exist. Monitoring and evaluation of current malaria transmission status is an important component of malaria control as it is a measure of the success of ongoing interventions and guides the planning of future control and elimination efforts. Main text We evaluated changes in malaria control policy in Ethiopia, and reviewed dynamics of country-wide confirmed and clinical malaria cases by Plasmodium species and reported deaths for all ages and less than five years from 2001 to 2016. Districts level annual parasite incidence was analysed to characterize the malaria transmission stratification as implemented by the Ministry of Health. We found that Ethiopia has experienced major changes from 2003 to 2005 and subsequent adjustment in malaria diagnosis, treatment and vector control policy. Malaria interventions have been intensified represented by the increased insecticide treated net (ITN) and indoor residual spraying (IRS) coverage, improved health services and improved malaria diagnosis. However, countrywide ITN and IRS coverages were low, with 64% ITN coverage in 2016 and IRS coverage of 92.5% in 2016 and only implemented in epidemic-prone areas of > 2500 m elevation. Clinical malaria incidence rate dropped from an average of 43.1 cases per 1000 population annually between 2001 and 2010 to 29.0 cases per 1000 population annually between 2011 and 2016. Malaria deaths decreased from 2.1 deaths per 100 000 people annually between 2001 and 2010 to 1.1 deaths per 100 000 people annually between 2011 to 2016. There was shrinkage in the malaria transmission map and high transmission is limited mainly to the western international border area. Proportion of P. falciparum malaria remained nearly unchanged from 2000 to 2016 indicating further efforts are needed to suppress transmission. Conclusions Malaria morbidity and mortality have been significantly reduced in Ethiopia since 2001, however, malaria case incidence is still high, and there were major gaps between ITN ownership and compliance in malarious areas. Additional efforts are needed to target the high transmission area of western Ethiopia to sustain the achievements made to date.